Effect of monensin on grain bloat in cattle - Coe, M.L.; Wallace, N.; Kemp, Kenneth E.; Parrott, J.C.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve ruminally cannulated Holstein steers were used to determine the effect of monensin (0, 20, 30, and 40 g/ton) on grain bloat. Steers were fed a bloat-provocative, high-grain diet at 1% of body weight twice daily. Monensin premix was added directly to individual steers diets at the time of feeding. The severity of bloat was scored daily on a scale of 0 (no bloat) to 5 (severe bloat). The scoring was based on the degree of frothiness and abdominal distention. Bloat scores (mean of wk 2, 3, and 4) were lower (P<.0l) for monensin-fed steers than for the controls. The mean bloat scores were 1.43, 1.18, 1.00, and .93 for 0, 20, 30 and 40 g/ton monensin, respectively. Total gas production during in vitro ruminal fermentation tended to be higher (P=.12) for control than for monensin-fed steers. Ruminal pH and total volatile fatty acid concentrations were unaffected by treatment. Monensin decreased frothy bloat caused by the bloat-provocative diet, and the degree of control appeared to be greater with higher levels of monensin.
Keywords: Beef; Monensin; High grain diet; Frothy bloat